A research framework for the United Nations Decade of Healthy Ageing (2021–2030) - Norah Keating (European Journal of Ageing, 2022)
The mission of UN Decade of Healthy Ageing (2020–2030) is to improve the lives of older people, their families and their communities. In this paper, we create a conceptual framework and research agenda for researchers to knowledge to address the Decade action items. The framework builds on the main components of healthy ageing: Environments (highlighting society and community) across life courses (of work and family) toward wellbeing (of individuals, family members and communities). Knowledge gaps are identified within each area as priority research actions. Within societal environments, interrogating beliefs about ageism and about familism are proposed as a way to illustrate how macro approaches to older people influence their experiences. We need to interrogate the extent to which communities are good places to grow old; and whether they have sufficient resources to be supportive to older residents. Further articulation of trajectories and turning points across the full span of work and of family life courses is proposed to better understand their diversities and the extent to which they lead to adequate financial and social resources in later life. Components of wellbeing are proposed to monitor improvement in the lives of older people, their families and communities. Researcher priorities can be informed by regional and national strategies reflecting Decade actions.